Rhetoric Analysis on the Relationship between Executive Compensation and Performance of Commercial public enterprises in Namibia. (International Journal of Scientific Research and Management (IJSRM), 2021)
The purpose of this paper was to investigate the relationship between compensation packages and the performance of executive officers in Commercial Public Enterprises in Namibia. The paper was conducted to achieve the following specific objective: to determine the relationship between compensation packages of executives and the performance of Commercial PEs in Namibia. It was all in the context of mixed research approach for data collection using a questionnaire as a tool. The study found that there is a partial relationship between executive compensation and the performance of some commercial public enterprises, in accordance with their Tier Levels. It is recommended that the Government (shareholder) finds the best fit model of executive compensation packages in order to induce a positive level of performance. It is further recommended that a study be conducted, to investigate the relationship between the role of an independent high-level committee on executive compensation packages, aimed at enhancing performance in Commercial Public Enterprises in Namibia Keywords: Compensation Package; Performance; Commercial Public Enterprises; Executives